Análisis de la cuenta inventario del negocio Electrocapri de la ciudad de Pasaje y su impacto en el ejercicio económico 2021. - Changkuon Romero, Yiang Fernando; Celi Carrillo, Jazmin Elizabeth (Universidad Técnica de Machala, 2022)
In the present investigation, it was possible to demonstrate the analysis of the effects of the inadequate inventory management of the company "Electrocapri" in the fiscal year of 2021, through the study and obtention of accounting information of the study company due to the fact that it is the internal and inventory control is relevant, for which a methodological design based on the qualitative approach has been implemented, which responds to a positivist paradigm; Therefore, it is necessary to establish a relationship between the researcher and the object of study, using the instrument of the interview directed towards the leader and employee, in addition to the application of an observatory file on the most relevant aspects of the phenomenon that occurs in the company. To which results were issued about the lack of knowledge of accounting culture and the absence of an internal inventory account control software, for which it is suggested that appropriate technological tools be implemented to the need of the stockroom to increase the index of productivity and improvement of inventory management.
En el presente trabajo se pudo evidenciar el análisis de los efectos de la inadecuada gestión de inventario de la empresa "Electrocapri" en el ejercicio económico del año 2021, a través del estudio y recopilación de información contable de la empresa de estudio debido a que es relevante el control interno y de inventario para lo cual se ha implementado un diseño metodológico basado en el enfoque cualitativo, que responde a un paradigma positivista; por lo que se necesita establecer una relación entre el investigador y el objeto de estudio. En uso del instrumento de la entrevista dirigida hacia el gerente y empleado, además de la aplicación de una ficha observatorio sobre los aspectos más relevantes del fenómeno que se presenta en la empresa, se emitieron resultados acerca de la falta de conocimiento de cultura contable y la ausencia de un software de control interno de cuenta de inventario, por lo cual se sugiere que se implementen herramientas tecnológicas apropiadas a la necesidad del almacén para incrementar el índice de productividad y el mejoramiento de la gestión de inventarios.
Keywords: CONTROL INTERNO; GESTION; ALMACEN